Land Degradation Issues in Nepal and Its Management Through Agroforestry - Acharya, Anil Kumar; Kafle, Narayan (Journal of Agriculture and Environment, 2009)
Land degradation is major challenge of Nepal. The paper focuses mainly on causes and consequences of land degradation and their management approaches. Land degradation may occur through different physical, chemical and biological processes induced directly or indirectly by human activities like deforestation, shifting cultivation, overgrazing, steep slope farming, over use of chemical fertilizers and forest resources. These create many social problems like poverty, poor health and nutrition and demographic dynamics by lowering agricultural productivity. Agroforestry approaches like use of Multi Purpose Tree Species (MPTs), relay-cropping, terracing and contour cultivation, strip and alley cropping are appropriate to fulfill the needs of low resource farmers by restoring and increasing land productivity. The potentiality of the approach can be made more effective through holistic efforts, based on needs with active participation of farmers in planning and implementation stage. Key Words: Biodiversity; Deforestation; Ecosystem; Natural resource; Productivity; Erosion The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 133-143